Acid ceramidase of macrophages traps herpes simplex virus in multivesicular bodies and protects from severe disease - Judith Lang (Nature Portfolio, 2020)
Macrophages are critical in limiting replication of herpes simplex virus type 1 (HSV-1). Here the authors show how acid ceramidase and its enzymatic product sphingosine enable multivesicular bodies to function as an anti-viral mechanism.